Organic Farming and Food Production - Konvalina, Petr (IntechOpen, 2012)
Organic farming does not mean going "back" to traditional (old) methods of farming. Many of the farming methods used in the past are still useful today. Organic farming takes the best of these and combines them with modern scientific knowledge. The goal was to write a book where as many different existing studies as possible could be presented in a single volume, making it easy for the reader to compare methods, results and conclusions. As a result, studies from countries such as Romania, Poland, The Czech Republic, Mexico, Slovenia, Finland, etc. have been compiled into one book. The opportunity to compare results and conclusions from different countries and continents will create a new perspective in organic farming and food production as well as help researchers and students from all over the world to attain new and interesting results in this field.